Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Review: 30

Answer

$-\frac{1}{4}$

Work Step by Step

$(-64)^{-\frac{1}{3}}=\frac{1}{(-64)^{\frac{1}{3}}}=\frac{1}{\sqrt[3] (-64)}=\frac{1}{(-4)}=-\frac{1}{4}$ We know that $\sqrt[3] (-64)=-4$, because $(-4)^{3}=-4\times-4\times-4=-64$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.